2022
DOI: 10.1007/s10862-022-09990-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Internalizing Symptoms and Anxiety Sensitivity Among College Students During the COVID-19 Pandemic

Abstract: The early months of the COVID-19 pandemic saw significant increases in symptoms of anxiety and depression, particularly among college students. However, research has not examined how internalizing symptoms in this population have changed as the pandemic has continued into its second year. Further, there has yet to be an examination of potential changes in transdiagnostic vulnerability factors. Therefore, the purpose of the current repeated cross-sectional study was to examine differences by term in undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In other words, social anxiety symptoms appeared to be exacerbated as restrictions eased for those who were socially anxious in the first place. Another study by McLeish et al [66] found that college students had increased social interaction anxiety when returning to a higher frequency of social encounters after a period of social isolation. In this study, data relating to social interaction anxiety were collected from college students across three time points after the onset of the pandemic.…”
Section: Mental Health Outcomes During Easing Of Restrictionsmentioning
confidence: 98%
“…In other words, social anxiety symptoms appeared to be exacerbated as restrictions eased for those who were socially anxious in the first place. Another study by McLeish et al [66] found that college students had increased social interaction anxiety when returning to a higher frequency of social encounters after a period of social isolation. In this study, data relating to social interaction anxiety were collected from college students across three time points after the onset of the pandemic.…”
Section: Mental Health Outcomes During Easing Of Restrictionsmentioning
confidence: 98%
“…One the one hand, reduced exposure to social situations may have assuaged their anxiety symptoms in the short term. Yet, because avoidance maintains social anxiety (e.g., Clark & Wells, 1995; Rapee & Heimberg, 1997), such reduced exposure may ultimately lead to an exacerbation of people's social anxiety symptoms over time and upon re‐entering social situations, consistent with emerging research (e.g., McLeish et al, 2022). In fact, a recent study found that undergraduates during the COVID‐19 pandemic maintained elevated social anxiety scores (Arad et al, 2021), which constrasts with pre‐pandemic findings, when social anxiety tended to decline across the academic year.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, it is possible that the widespread experience of anticipatory anxiety may not only have caused short term distress, but also sustained people's social fears and increased their likelihood of prolonged avoidance. Emerging evidence is consistent with this reasoning, with multiple studies reporting increased social anxiety symptoms across the COVID‐19 pandemic (e.g., Arad, Shamai‐Leshem, & Bar‐Haim, 2021; McLeish, Walker, & Hart, 2022; Thompson et al, 2021; cf. Langhammer, Peters, Ertle, Hilbert, & Leuken, 2022).…”
Section: Introductionmentioning
confidence: 89%
“…There was a high prevalence of social anxiety throughout the pandemic [ 60 ]. After completing their courses through Zoom, students had to relearn interactions with others, with the added stresses of social distancing guidelines.…”
Section: Resultsmentioning
confidence: 99%